Pengolahan Abon Ikan Tongkol (Euthynnus affinis) Sebagai Sumber Protein Alternatif Tinggi Dengan Penambahan Daun Jeruk Purut Untuk Meningkatkan Kualitas Sensori - Atika Ulfiya Adlina; Kurnia Latifatun Nikmah; Wahyu Qomaruddin; Shofwatun Nada (Politeknik Negeri Ketapang, 2026)
This study aims to develop tuna fish floss (Euthynnus affinis) as an alternative high-protein food with the addition of kaffir lime leaves (Citrus hystrix) to improve sensory quality. The research method used a Simple Randomized Design (RAS) with two treatments, namely control (0%) and the addition of 5% kaffir lime leaves. The stages of the study included preparation of materials, making floss, and organoleptic testing by 20 panelists based on color, taste, aroma, and texture. The results showed that the addition of kaffir lime leaves significantly improved the taste, aroma, and texture of tuna fish floss, while the color was preferred in the treatment without kaffir lime leaves. This product has the potential to be a source of nutritious alternative protein with added economic value and business opportunities in the field of fishery product processing.